The cellular heat shock response monitored by chemical exchange saturation transfer MRI - Kleimaier, Dennis; Görke, Steffen; Nies, Cordula; Zaiss, Moritz; Kunz, Patrick; Bachert, Peter; Ladd, Mark E.; Gottwald, Eric; Schad, Lothar R. (Scientific reports, 2020)
CEST-MRI of the rNOE signal has been demonstrated in vitro to be closely linked to the protein conformational state. As the detectability of denaturation and aggregation processes on a physiologically relevant scale in living organisms has yet to be verified, the aim of this study was to perform heat-shock experiments with living cells to monitor the cellular heat-shock response of the rNOE CEST signal. Cancer cells (HepG2) were dynamically investigated after a mild, non-lethal heat-shock of 42 °C for 20 min using an MR-compatible bioreactor system at 9.4 T. Reliable and fast high-resolution CEST imaging was realized by a relaxation-compensated 2-point contrast metric. After the heat-shock, a substantial decrease of the rNOE CEST signal by 8.0 ± 0.4% followed by a steady signal recovery within a time of 99.1 ± 1.3 min was observed in two independent trials. This continuous signal recovery is in coherence with chaperone-induced refolding of heat-shock induced protein aggregates. We demonstrated that protein denaturation processes influence the CEST-MRI signal on a physiologically relevant scale. Thus, the protein folding state is, along with concentration changes, a relevant physiological parameter for the interpretation of CEST signal changes in diseases that are associated with pathological changes in protein expression, like cancer and neurodegenerative diseases.